Manajemen Risiko Dana Tabarru PT. Asuransi Jiwa Syariah Al Amin - Saniatusilma, Hifi; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this study is to find out the risk management of tabarru funds. As anÂ institution that works to manage risk, islamic insurance has a duty to manage the tabarruâÂ funds. There is the possibility of a risk at tabarruâ fund. So, islamic insurance institution have aÂ duty for risk management process of tabarruâ funds. This study uses a qualitative approach.Â Data research obtained by interview and documentation with the head and the deputy ofÂ Al Amin Surabaya branch. The results of this study, PT. Asuransi Jiwa Syariah Al Amin wasÂ execute the risk management process implemented by the four stages. Risk identificationÂ through underwriting limit process; rank the risk based on impact and complexity of risk;control risks by self retention; and response to the risk through change of insurance rates,Â products diversification and sharing of risk with reinsurance.